Does audit fee stickiness and audit quality are reciprocal? - Slamet Wahyudi (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
This study examines the relationship between audit fee stickiness and audit quality to determine whether they mutually affect each other. Using panel data and fixed-effects as well as common-effects regression methods, the study evaluates how total assets, leverage, audit changes, and the Covid-19 pandemic influence both variables. This methodology was chosen for its ability to control for individual differences and handle panel data, allowing for a more accurate analysis of the relationship between audit fee rigidity and audit quality. The main findings show that total assets and audit changes have a significant positive effect on audit fee stickiness, while the Covid-19 pandemic does not significantly affect audit fee stickiness. Additionally, total assets and leverage have a significant positive impact on audit quality, whereas audit changes do not influence audit quality and the Covid-19 pandemic actually improves audit quality. Although audit fee stickiness contributes to the enhancement of audit quality, audit quality does not have a significant effect on audit fee stickiness, indicating that there is no reciprocal relationship between the two. The study suggests the need for adjustments in the audit fee setting mechanism to ensure that audit quality is maintained optimally without being influenced by fee rigidity.